2012
DOI: 10.1073/pnas.1220168110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of natural variation reveals neurogenetic networks forDrosophilaolfactory behavior

Abstract: Understanding the relationship between genetic variation and phenotypic variation for quantitative traits is necessary for predicting responses to natural and artificial selection and disease risk in human populations, but is challenging because of large sample sizes required to detect and validate loci with small effects. Here, we used the inbred, sequenced, wild-derived lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) to perform three complementary genome-wide association (GWA) studies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
105
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(114 citation statements)
references
References 55 publications
8
105
1
Order By: Relevance
“…One interpretation of our results is that the ORN expressing Or42b, which is activated by acetal, and the ORN expressing Or33b, which is activated by 2,5-dimethylpyrazine, do not belong to a single equivalence class; that is, they may play distinguishable roles in driving olfactory behavior. Although our results support a model in which many ORNs can activate an attraction response, their connectivity may not be functionally identical (43). Different ORNs may contribute differently to the modulation of the runs and turns of navigation behavior or to feeding decisions.…”
Section: Discussioncontrasting
confidence: 87%
“…One interpretation of our results is that the ORN expressing Or42b, which is activated by acetal, and the ORN expressing Or33b, which is activated by 2,5-dimethylpyrazine, do not belong to a single equivalence class; that is, they may play distinguishable roles in driving olfactory behavior. Although our results support a model in which many ORNs can activate an attraction response, their connectivity may not be functionally identical (43). Different ORNs may contribute differently to the modulation of the runs and turns of navigation behavior or to feeding decisions.…”
Section: Discussioncontrasting
confidence: 87%
“…To test this, we generated various Drosophila flies with mutations in PKC genes rather than in Orco itself. PKC53E and PKCδ are genes that could be involved in OSN signal transduction (Swarup et al, 2013;Arya et al, 2015). Here, we found that null mutations of both conventional PKC53E and novel PKCδ or suppression of PKC53E and PKCδ genes using RNAi shifted the concentration-response of the OSNs to higher odour concentrations compared with wild-type (P<0.05; Fig.…”
Section: Pkc Increases Osn Sensitivity To Brief and Intermittent Odoumentioning
confidence: 67%
“…Insect olfactory systems express diverse calcium-and cyclic nucleotide-activated kinases (Schaeffer et al, 1989;Chintapalli et al, 2007;Tunstall et al, 2012), yet any role in signal transduction is unknown. Members of the protein kinase C family (PKCs), in particular, are network genes found to play a role in insect signal transduction, neural connectivity and natural variation in olfactory behaviour (Swarup et al, 2013;Arya et al, 2015). Here, we propose that PKC-mediated intracellular signalling in the recently evolved ORs offers a mechanistic advantage to detect and respond to the brief and intermittent odour information received while tracking plume information in flight.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Drosophila mutations (33) and natural variants (37) on aggression depend on genetic background, a phenomenon also observed for mutations in neuronal nitric oxide synthase (38) and Nr2e1 (16) in mice. Analysis of naturally segregating variation can leverage polymorphisms at many loci to explore the contribution of epistatic interactions to genetic variation for complex traits (39)(40)(41).…”
mentioning
confidence: 99%